MO712EVALUATION OF VOLUME OVERLOAD STATUS MARKERS IN PERITONEAL DIALYSIS PATIENTS. (29th May 2021) - Carvão, João; Fernandes, Adriana; Veríssimo, Rita; Calça, Rita; Martins, Ana Rita; Matias, Patricia; Branco, Patricia
Abstract: Background and Aims: N-terminal fragment of B-type natriuretic peptide (NT-proBNP) can reflect changes in hydration status and may help the nephrologist to estimate it. Fluid volume overload is a major concern in dialysis patients, and it is associated with increased cardiovascular risk and death. This study evaluated the relationship between serum NT-proBNP levels and left ventricular (LV) dysfunction and extra-cellular excess water in peritoneal dialysis patients. Method: We conducted a cross-sectional study of 60 peritoneal dialysis (PD) patients. Incident and prevalent patients were included. Echocardiography was performed using HDI 5000, allowing M-mode, two-dimensional measurement. A multifrequency bioimpedance (BIA) analyzer was used. Overhydration (OH) was defined as an extra-cellular water (ECW)/total body water (TBW) over 15%. Clinical and biochemical variables were also analysed. Results: A total of 60 patients were evaluated (male 60% (n=36), mean age was 55, 8 ± 15, 3 years, BMI 25.9 ± 3.9 kg/m2 and 31.7% (n=19) had diabetes mellitus (DM). Median PD vintage was 21 months, automated PD 30%, 8.3% (n=5) were anuric and 10% (n=6) were overhydrated. The median serum NT-proBNP level was 1071 pg/mL. LV mass index and LV ejection fraction were 129.0 ± 51.1 g/m2 and 62.8 ± 13.0%, respectively. The median excess volume overload was 0.9L. Serum NT-proBNP levels correlated positively with, diabetes (r=0.27, p=0.04), isquemic cardiopathy (r=0.37, p=0.01), LV mass index (r=0.48, p=0.001) and extracellular water (r=0.31, p=0.02) and negatively with LV ejection fraction (r= -0.81, p=0.01). In a multivariable analysis, in a model adjusted to time in DP, diabetes, residual diuresis, isquemic cardiopathy and left ventricle mass index, NT-proBNP > 1600 pg/mL was associated with patient overhidratation (exp (B) 1, 44, 95% CI 0, 15-2.73). No statistical difference was observed considering nutritional parameters, peritoneal transport, dialysis efficacy and NT-proBNP. Conclusion: In this population, higher levels of NT-proBNP were associated with overhydration status and left ventricular dysfunction. Therefore, BIA and NT-proBNP may be complementary to clinical evaluation of PD patients. BIA results can be affected by malnutrition with loss of cell mass according to some studies. In our population NT-proBNP is not affected by nutritional status and therefore can also be used as a congestive marker in malnourished patients. Longitudinal application of BIA could be a useful clinical tool to evaluate adequacy in PD patients.